Model pembelajaran pelafalan dengan metode verbo-tonal dalam pembelajaran bahasa Perancis - Hardini, Tri Indri; Sunendar, Dadang; Mutiarsih, Yuliarti; Lorenzi, Analeila Devira (Jurnal Pendidikan Bahasa dan Sastra, 2021)
This research was conducted in the context of developing a learning model with the verbo-tonal method of phonetic correction in pronunciation learning for French language learning students at levels A1 and A2 CECRL (Cadre européen commun de référence pour les langues / The Common European Framework of Reference for Languages). This study aims to describe: (1) the steps of the learning model with the verbo-tonal method in learning French pronunciation for levels A1 and A2 CECRL (2) the flow of pronunciation learning for French learners for levels A1 and A2 CECRL by applying the verb method -tonal (3) the advantages and disadvantages of pronunciation learning models with the verbo tonal method. Researchers used a quantitative approach methodology with the Research Development (RD) method in developing a verbo-tonal method of phonetic correction. The population in this study were all the characteristics of the French Language Study Program students at FPBS UPI. While the sample in this study were all the characteristics that exist in French language learning students at the A1 and A2 CECRL levels in the French Language Education Study Program, FPBS UPI who were selected by purposive sampling technique.